Protocol on establishing a prospective enhanced surveillance of vaccine preventable diseases in residential aged care facilities in Central Queensland, Australia: an observational study. Issue 6 (3rd June 2022) - Hashan, Mohammad Rashidul; Chapman, Gwenda; Walker, Jacina; Jayne Davidson, Sonya; Auriac, Jill; Smoll, Nicolas; Kirk, Michael; Akbar, Delwar; Booy, Robert; Khandaker, Gulam
Abstract : Introduction: Infectious diseases are a major cause of mortality and morbidity among the highly vulnerable occupants of residential aged care facilities (RACFs). The burden of vaccine preventable diseases (VPDs) among RACFs residents is mostly unknown and there is a lack of quality data from population-based prospective VPD surveillance in RACFs. The increasing burden of emerging and existing VPDs (eg, COVID-19, influenza, pneumococcal, pertussis and varicella-zoster) necessitates the establishment of an active enhanced surveillance system to provide real-time evidence to devise strategies to reduce the burden of VPDs in RACFs. Method and analysis: This study proposes a prospective active enhanced surveillance that will be implemented in RACFs across the Central Queensland (CQ) region. The study aims to measure the burden, identify aetiologies, risk factors, predictors of severe outcomes (eg, hospitalisations, mortality) and impact of the existing National Immunization Program (NIP) funded vaccines in preventing VPDs in this vulnerable population. CQ Public Health Unit (CQPHU) will implement the active surveillance by collecting demographic, clinical, pathological, diagnostic, therapeutic and clinical outcome data from the RACFs based on predefined selection criteria and case report forms as per routine public health practices. Descriptive statistics, univariate and multivariate regression analysis will be conducted to identify the predictors of morbidity and clinical outcomes following infection. Ethics and dissemination: The study has been approved by the CQHHS Human Research Ethics Committee (HREC) (reference number HREC/2021/QCQ/74305). This study involves data that is routinely collected as part of the surveillance of notifiable conditions under the Public Health Act 2005. The CQHHS HREC approved a request to waive consent requirements of study participants as researchers will be provided non-identifiable data. The findings from the study will be actively disseminated through publication in peer-reviewed journals, conference presentations, social and print media, federal, state, and local authorities to reflect on the results that may facilitate revision of policy and highlight the stakeholders, funding bodies both locally and internationally.